Two new species of the genus Uenoites Belousov et Kabak, 2016 from mountains of Myanmar (Coleoptera: Carabidae: Trechini) - Belousov, Igor A.; Kabak, Ilya I.; Schmidt, Joachim (Zootaxa, 2019)
Two new species of ground beetles of the genus Uenoites Belousov et Kabak, 2016 (tribe Trechini) are described from mountains of northern Myanmar: U. reuteri sp. n., and U. tibialis sp. n.. There are the first members of the genus found outside Yunnan Province of China. The taxonomic position of the new species within the genus is discussed based on the relevant character states in external and genital morphology. Both newly described species are closely related to each other and seem to form a distinct species-group within extremely diverse genus Uenoites. Externally, the newly described species are much more similar to very large members of the genus Queinnectrechus Deuve, 1992, than to most Uenoites but differs in an increased number of elytral setiferous pores in stria 3 and in the presence of the preapical pore.